(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
Quality of life (QoL) refers to an assessment of disease-associated and non-associated parameters, and allows differentiating the impact of disease and treatment on the patient’s psychological, emotional state, and social status. The aim of the study was to estimate the quality of life in patients with chronic heart failure (CHF) with preserved cardiac output.